Sensitivity evaluation of a single-step PCR assay using Ehrlichia canis p28 gene as a target and its application in diagnosis of canine ehrlichiosis - Nakaghi, Andrea Cristina Higa [UNESP]; Machado, Rosangela Zacarias [UNESP]; Ferro, Jesus Aparecido [UNESP]; Labruna, Marcelo Bahia; Chryssafidis, Andreas Lazaros; André, Marcos Rogério [UNESP]; Baldani, Cristiane Divan [UNESP] (Colégio Brasileiro de Parasitologia Veterinária, 2010)
O objetivo deste estudo foi aperfeiçoar um ensaio de PCR que amplificasse um fragmento de 843 pares de bases do gene p28 da Ehrlichia canis e compará-lo com outros dois métodos de PCR utilizados para amplificar partes do gene 16S rRNA e dsb do gênero Ehrlichia. Amostras sanguíneas foram colhidas de cães com diagnóstico clínico de erliquiose. A amplificação do gene p28 pela PCR produziu um fragmento de 843pb e esse ensaio permitiu a detecção do DNA de um parasita dentre 1 bilhão de células. Todas as amostras positivas detectadas pela PCR baseada no gene p28 foram também positivas pela nested PCR para detecção do gene 16S rRNA e também pela PCR dsb. Dentre as amostras negativas para a PCR p28, 55,3% foram co-negativas, mas 27,6% foram positivas pela PCR baseada nos genes 16S rRNA e dsb. A PCR p28 parece ser um teste útil para detecção molecular de E. canis, entretanto otimizações na sensibilidade nesta PCR são necessárias, para que esta técnica se torne uma importante alternativa no diagnóstico da erliquiose canina.

The aim of this study was to optimize a PCR assay that amplifies an 843 pb fragment from the p28 gene of Ehrlichia canis and compare it with two other PCR methods used to amplify portions of the 16S rRNA and dsb genes of Ehrlichia. Blood samples were collected from dogs suspected of having a positive diagnosis for canine ehrlichiosis. Amplification of the p28 gene by PCR produced an 843-bp fragment and this assay could detect DNA from one gene copy among 1 billion cells. All positive samples detected by the p28-based PCR were also positive by the 16S rRNA nested-PCR and also by the dsb-based PCR. Among the p28-based PCR negative samples, 55.3% were co-negatives, but 27.6% were positive in 16S rRNA and dsb based PCR assays. The p28-based PCR seems to be a useful test for the molecular detection of E. canis, however improvements in this PCR sensitivity are desired, so that it can become an important alternative in the diagnosis of canine ehrlichiosis.
Avaliação da sensibilidade da PCR em uma etapa com base no gene p28 de Ehrlichia canis e sua aplicação no diagnóstico da erliquiose canina
Keywords: Ehrichia canis; PCR; p28; gene dsb; gene 16S rRNA; Ehrlichia canis; PCR; p28; dsb gene; 16S rRNA gene